The effects of attribute persistence on cooperation in evolutionary games. (October 2018) - Yang, Kai; Huang, Changwei; Dai, Qionglin; Yang, Junzhong
Highlights: By considering strategy-updating rule as an attribute of players, the influence of attribute persistence on cooperation in evolutionary games is investigated. Frequent alternation of attribute improves the conformity-enhanced network reciprocity for the unbiased rule. The aspiration rule for alternation of attribute is invalid in improving conformity-enhanced network reciprocity. Abstract: In ordinary evolutionary game theory, players update their strategies according to a certain payoff-driven rule. Szolnoki and Perc (2015) [44] found conformity-enhanced network reciprocity by introducing conformity-driven strategy-updating rule to an appropriate fraction of players. In this work, we treat strategy-updating rule as an attribute of players and allow for the evolution of the attribute, for example, the alternation of the strategy-updating rule between payoff-driven and conformity-driven rules with time. We introduce the persistence parameter T by assuming that players change their strategy-updating rules every T Monte Carlo time unit according to either unbiased rule or aspiration rule. We find that frequent alternation of strategy-updating rule improves the conformity-enhanced network reciprocity for the unbiased rule, which leads that small T greatly promotes cooperation. On the other hand, we find no improvement of conformity-enhanced network reciprocity for the aspiration rule.